PENGARUH PENERAPAN AKUNTANSI MANAJEMEN DAN SISTEM INFORMASI AKUNTANSI TERHADAP EFEKTIVITAS PENGENDALIAN BIAYA PADA LEMBAGA KEUANGAN KELURAHAN DI KOTA MADIUN - Siti Suharni; Mohammad Sofyan; Andri Hasmoro Kusumo Broto (Universitas Merdeka Madiun, 2026)
This study aims to analyze the influence of management accounting practices and accounting information systems on cost control effectiveness. A quantitative approach was employed using partial least squares-structural equation modeling (PLS-SEM). Management accounting practices were measured through four key indicators, while the accounting information systems was assessed using five system quality dimension. Cost sontrol effectiveness was evaluated through five indicators representing operational cost sontrol performance. The findings reveal that management accounting practices have a positive and significant effect on cost control effectiveness, although the magnitude of the effect is relatively small. In contrast, the accounting information system demonstrate a very strong and significant influence on cost sontrol effectiveness, with the higest path coefficient and a substantial effect size. The adjusted R2 value of 0.808 and Q2 value of 0.569 indicate that the model prosesses strong explanatory and predictive power. There results highlight that, in the digital era, cost control effectiveness is largely determined by the quality of accounting information systems that provide accurate, timely, integrated, and user-friendly information, while management accounting practices function as a complementary mechanism that enhances the utilization such information. This study suggest that organizations should prioritize the development of modern and integrated accounting information to strngthen cost control effectiveness.